INTERNATIONAL INNOVATIONS IN MEDICAL ROBOTICS TO IMPROVE THE PATIENT MANAGEMENT IN PERU: INNOVACIONES INTERNACIONALES EN ROBÓTICA MÉDICA PARA MEJORAR EL MANEJO DEL PACIENTE EN PERÚ - Cornejo, José (2019)
Surgical Engineering Society conducted a research, the First Review as the pioneers in LATAM, since year 2015, which develops the topic of the latest Medical Robotics technologies created in North América, Europe and Asia, which are imported to apply in the Healthcare System of Peru and Latin America. The robotic systems for surgery, rehabilitation and assistance are presented covering the description of control design and technical specifications. Besides, the patient management using robots is analyzed with diagnosis, prognosis and treatment tools. The process to evaluate the new inventions of robotic devices and bring to the market is introduced where three stages are shown as the following: innovation, regulatory affairs and biomedical application. Moreover, there is a high percentage of population with disability in Latin America, therefore, it is necessary that more biomedical scientists be specialized in robotics to start developing new ideas to improve the patient management. Finally, the new technologies created in Latin America must be affordable, simply and efficient in order to support the healthcare economic situation in the continent and give the best quality standards to improve treatment outcomes on patients.